Eigenstate equivalent circuit for bi-periodic surfaces: Application to three parallel dipoles - Hernández Escobar, Alberto; Abdo-Sánchez, María Elena; Esteban Marzo, Jaime; Martín-Guerrero, Teresa María; Camacho-Peñalosa, Carlos (My University, 2022)
An equivalent circuit for the unit cell of bi-periodic surfaces is proposed. The equivalent circuit is general and simple. It is based on the decomposition of the eigenmodes of the structure and it takes into account the polarization of the incident wave. It consists of the interconnection of two different admittances and two transformers. The model of a unit cell composed of three parallel dipoles is extracted. The transformer of the proposed equivalent circuit models the rotation of the dipoles, while the admittances model their frequency behaviour (resonances). This equivalent circuit provides physical insight and, at the same time, it models in separate elements the contribution of the rotation and the dipole trio resonances. The model is able to replicate the full-wave simulation result with great accuracy.
Keywords: Circuitos electrónicos - Diseño; Antenas - Diseño y construcción; Electromagnetismo; Circuito Equivalente; Autovalores; Reflector de polarización